Triacylglycerol and wax ester-accumulating machinery in prokaryotes - Alvarez, Hector Manuel (2016)
Gram negative bacteria as well as Gram positive actinobacteria possess the ability to accumulate variable amounts of wax esters (WE) and/or triacylglycerols (TAG) under nitrogen limiting conditions. In recent years many advances have been made to obtain insight into neutral lipid biosynthesis and accumulation in prokaryotes. The clinical and industrial relevance of bacterial WE/TAG significantly promoted basic and applied research in this field. The recent integrated omic studies as well as the functional characterization of diverse genes are contributing to unravel the composition of the WE/TAG-accumulating machinery in bacteria. This will be a valuable data for designing new drugs against bacteria with clinical importance, such as Mycobacterium tuberculosis, or for transferring and optimizing lipid accumulation in bacterial hosts naturally unable to produce such lipids, such as Escherichia coli. In this article, recent investigations addressing WE/TAG biosynthesis and storage in prokaryotes are presented. A comprehensive view of the current knowledge on the different genes/proteins involved in WE/TAG biosynthesis is included.